Narrative Transportation's Role in Shaping Travel Intentions: A Study on Persuasiveness and Net Zero Commitments - Chang, Chee Heng (Curtin University, 2025)
This thesis investigates the role of narrative transportation in shaping travel intentions, with a focus on persuasiveness and net-zero commitments. The study addresses the problem of ineffective marketing strategies for cultural heritage destinations in Malaysia, which face challenges in promoting lesser-known cultural heritage sites. This research contributes to the practical by developing a comprehensive conceptual framework, serving as guidelines for destination marketing organisations to implement digital storytelling effectively.